Hospital scheduling analysis: a contemporary review and proposed schematic understanding - Ali, Hussein Hasan; Lamsali, Hendrik; Othman, Siti Norezam (JARDCS, 2018)
Hospital scheduling presents huge challenges for the healthcare industry. Various studies have been conducted in many different countries with a focus on both elective and non-elective surgeries. There are important variables and factors that need to be taken into considerations. Different methods and approaches have also been used to examine hospital scheduling. Notwithstanding the continuous changes in modern healthcare services and, in particular, hospital operations, consistent reviews and further studies are still required. The importance of hospital scheduling, particularly, has become more critical as the trade-off between limited resources and overwhelming demand is becoming more and more evident. Hence, this study was carried out to identify and review previous works in relation to hospital scheduling. The aims were twofold: (1) to determine contemporary research as well as trends in hospital scheduling, and (2) to identify potential gaps for future study. The study focused on important components that included nursing, the operations room, and emergency and outpatient departments. A schematic diagram was then proposed to depict the general flow of hospital scheduling. The study concluded with the identification of potential research gaps for future study. This study is expected to contribute towards a better understanding of the key scheduling operations of hospitals and further undertakings of the relevant administrators.